Science Café as a Gateway for Adult Learning: A Brief Systematic Literature Review - Chynar Amanova (Adult Education Research Conference, 2022)
This paper provided a review of the studies on science cafés with the purpose of drawing attention of higher education practitioners to the importance of cafés in educating adult population.
Keywords: adult education; informal learning; science café